The right to a job, the right types of projects: employment guarantee policies from a gender perspective - Rania Antonopoulos (Levy Economics Institute of Bard College, 2007)
There is now widespread recognition that in most countries, private-sector investment has not been able to absorb surplus labor. This is all the more the case for poor unskilled people. Public works programs and employment guarantee schemes in South Africa, India, and other countries provide jobs while creating public assets. In addition to physical infrastructure, an area that has immense potential to create much-needed jobs is that of social service delivery and social infrastructure. While unemployment and enforced idleness persist, existing time-use survey data reveal that people around the worldespecially women and childrenspend long hours performing unpaid work. This work includes not only household maintenance and care provisioning for family members and communities, but also time spent that helps fill public infrastructural gapsfor example, in the energy, health, and education sectors. This paper suggests that, by bringing together public job creation, on the one hand, and unpaid work, on the other, well-designed employment guarantee policies can promote job creation, gender equality, and pro-poor development.
Keywords: B5; E24; E61; E62; H1; J16; 330; Unemployment; Poverty; Employer of Last Resort; Employment Guarantee Schemes; Gender; Household Production; South Africa